Accuracy of Siri and Brozek equations in the percent body fat estimation in older adults - R. S. Guerra (2010)
To identify which equation, Siri or Brozek, based on the two compartment model, provides a more accurate conversion of body density (BD) in percent body fat (%BF) in a group of older adults. Cross-sectional study. Research Centre in Physical Activity, Health and Leisure, Faculty of Sport, University of Porto. 60 older adults, aged 60-92 years. Skinfold thickness was used to estimate BD through Visser et al. prediction equation. The conversion of BD to %BF was done with Siri (%BF-Siri) and Brozek (%BF-Brozek) formulas and these determined values were both compared to Dual-Energy X-ray Absorptiometry (%BF-DXA) evaluations. A strong correlation between the %BF-DXA value and %BF-Siri (r=0.91, p < 0.001) and %BF-Brozek (r=0.91, p < 0.001) was found, although %BF-Siri and %BF-Brozek overestimated %BF-DXA (p < 0.001). The comparison of the %BF-Siri and %BF-Brozek mean values also revealed significant differences (p < 0.001). The %BF-Brozek reflects a better agreement than the %BF-Siri with %BF-DXA with respectively a mean difference of -4.0%BF (limits of agreement = -10.9 to 2.9%) and -5.7%BF (-12.6 to 1.2). The Bland and Altman plots confirmed that %BF-Brozek reflects a better agreement with %BF-DXA. The results of the present study show that the use of Brozek equation may correspond to a more accurate alternative than Siri equation for the conversion of BD in %BF in older adults.